B cell-rich non-neoplastic sentinel lesion preceding primary central nervous system lymphoma - Rodrigo Javier; Nawal Shaikh; Maciej S. Lesniak; Adam Sonabend; Roger Stupp; Amir Behdad; Craig Horbinski (BMC, 2018)
Abstract Background Primary central nervous system lymphoma (PCNSL) is an uncommon tumor in the brain. Although most PCNSL are readily diagnosed as diffuse large B cell lymphoma (DLBCL) on the first biopsy, very rare cases have been described in which the first detected intracerebral lesions are non-neoplastic, and are composed mostly of perivascular T cells, not B cells. This phenomenon is known as "sentinel lesions."